Genetic characterization of bovine herpesvirus 1 (BoHV-1) isolates from India - Patil, S S; Hemadri, D; Sreekala, K; Veeresh, H; Chandranaik, B M; Prabhudas, K (The Indian Journal of Animal Sciences, 2012)
Two bovine herpesvirus-1 (BoHV-1) isolates previously recovered from 2 animals showing different clinical symptoms, i.e. respiratory disease and balanoposthitis, were partially nucleotide sequenced at the gB gene. Aligned nucleotide sequences revealed high degree of identity among all the alphaherpesviruses compared in the study. The nucleotide sequence identity among the Indian isolates varied from 99–99.5% and so was their identity with reference Cooper strain. The phylogenetic analysis indicated that both the isolates belonged to subtype 1.1 despite being isolated from animals with different clinical manifestations.